The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m607249200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Myosin Heavy Chain Gene Regulation in Slow Skeletal Muscle

Abstract: The evolutionarily conserved order of the skeletal muscle myosin heavy chain (MHC) genes and their close tandem proximity on the same chromosome are intriguing and may be important for their coordinated regulation. We investigated type II MHC gene regulation in slow-type muscle fibers undergoing a slow to fast MHC transformation in response to inactivity, 7 days after spinal cord isolation (SI) in rats. We examined the transcriptional products of both the sense and antisense strands across the IIa-IIx-IIb MHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
52
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 46 publications
8
52
0
Order By: Relevance
“…In the present study, however, we performed a more detailed analysis of the slow, hybrid, and fast fibers at both immunohistochemical and mRNA levels, examining also the size (atrophy state) of the different fiber populations, because these data are necessary for judging the reinnervation level of fibers before the induction of regeneration. Our new results, namely the significantly high number of I/II hybrids, as well as the increase in the number of both MHCIIA-or MHCIIX-expressing fibers, accompanied by respective changes in their mRNA levels, suggest a gradual slow-to-fast fiber switch in reinnervated soleus, which is regulated predominantly at the mRNA level (Schiaffino and Reggiani 1996;Baldwin and Haddad 2001;Pandorf et al 2006).…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, however, we performed a more detailed analysis of the slow, hybrid, and fast fibers at both immunohistochemical and mRNA levels, examining also the size (atrophy state) of the different fiber populations, because these data are necessary for judging the reinnervation level of fibers before the induction of regeneration. Our new results, namely the significantly high number of I/II hybrids, as well as the increase in the number of both MHCIIA-or MHCIIX-expressing fibers, accompanied by respective changes in their mRNA levels, suggest a gradual slow-to-fast fiber switch in reinnervated soleus, which is regulated predominantly at the mRNA level (Schiaffino and Reggiani 1996;Baldwin and Haddad 2001;Pandorf et al 2006).…”
Section: Discussionmentioning
confidence: 63%
“…Although the exact role of this anti-sense transcript is not yet understood, it has been found to be associated with MHC isoform switching in the heart in response to pathologic stimuli, such as hemodynamic overload and diabetes [35][36][37]. A similar anti-sense mediated regulation of the MHC genes has also been suggested for isoform switching in slow skeletal muscle fibers [38].…”
Section: Regulation Of Mhc Gene Expressionmentioning
confidence: 94%
“…The genomic order, relative spacing, and the coding sequence are highly conserved across a broad evolutionary span. We have previously shown that functional significance for this gene order and intergenic spacing is apparent by the transcriptional coordination of MHC genes with long noncoding RNA transcripts that are transcribed in the antisense orientation to the IIa, IIx, and IIb MHC genes during alterations to muscle loading state (42,47). For example, muscle inactivity and unloading induce a coordinated IIa to IIx MHC shift in the soleus muscle whereby IIa decreases while IIx increases concurrently.…”
mentioning
confidence: 99%
“…For example, muscle inactivity and unloading induce a coordinated IIa to IIx MHC shift in the soleus muscle whereby IIa decreases while IIx increases concurrently. Along with these shifts, an antisense transcript is also induced, the so-called aII natural antisense transcript (NAT), which is transcribed in reverse orientation across the entire length of the IIa MHC gene (42). The aII NAT appears to repress IIa MHC gene transcription (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation